The Performance Enhancement Attitude Scale in Team Sports; Validity and Reliability Study - Uysal, Yucel; Toros, Turhan; Cetin, Mehmet Cagri; Ozyol, Funda Coskun; Serin, Emre; Guzel, Sinan; Ozturk, Rabia Yildiz (Progress in Nutrition, 2022)
Study Objectives: The aim of this study was to evaluate performance enhancement attitudes of active licensed athletes in team sports. Methods: The research sample of this study consists of 371 actively licensed athletes aged 18 and over in team sports (football, basketball, volleyball, and handball). The average age of the athletes is 24.42 ± 2.12. Participation in the study was carried out on a voluntary and confidential basis. Performance Enhancement Attitude Scale, developed by Petroczi (2002) and adapted to Turkish by Yıldız & Toros (2018), was used as a data collection tool. Results: In the analysis of the data, the Cronbach alpha coefficient test and the Pearson Correlation Coefficient were used to reveal the test-retest value. The Cronbach alpha coefficient for the team athletes of the scale was 0.84, and the test-retest reliability coefficient was 0.88. Conclusion: According to the research findings, the results of the reliability analysis reveal that the scale can be used on licensed athletes in team sports.